Characterization and fungicide sensitivity of Trichoderma species causing green mold of Ganoderma sichuanense in China - Li, Xuefei; Sossah, Frederick Leo; Tuo, Yonglan; Hu, Jiajun; Wei, Qian; Li, Shiyu; Rong, Na; Wiafe-Kwagyan, Michael; Li, Changtian; Zhang, Bo; Li, Xiao; Li, Yu (Frontiers in Microbiology, 2023)
This study focused on the investigation of green mold disease caused by Trichoderma species in Ganoderma sichuanense, an important mushroom in China. A survey was conducted in Zhejiang, Hubei, and Jilin Province, China, and 47 Trichoderma strains were isolated from necrotic G. sichuanense fruiting bodies displaying green mold symptoms. Through morphological and phylogenetic analysis, these isolates were classified into nine Trichoderma species as T. asperellum, T. citrinoviride, T. ganodermatiderum, T. guizhouense, T. hamatum, T. harzianum, T. koningiopsis, T. paratroviride, and T. virens, which were identified as pathogens causing green mold disease in G. sichuanense for the first time. Pathogenicity tests confirmed their role as pathogens through inoculation of healthy G. sichuanense fruiting bodies, followed by pathogen re-isolation and identification. The study also examined the sensitivity of the nine Trichoderma species to six fungicides. Prochloraz manganese showed the best performance against most species. This research contributes to our understanding of green mold disease, reveals the phylogenetic relationships among Trichoderma species, and expands our knowledge of Trichoderma species diversity associated with green mold disease in G. sichuanense.